ROCK MASS RATING OF CAVITY LIMESTONE LAYER IN REMBANG, CENTRAL JAVA, INDONESIA - R. Andy Erwin Wijaya; Dwikorita Karnawati; Srijono Srijono; Wahyu Wilopo (Geological Engineering Department Universitas Gadjah Mada, 2015)
mine design. Mine design is determined by the rock mass quality, which varies from one mine location to another, depending on the geological conditions. The research area is located in limestone quarry of Sale District, Rembang Regency, Central Java Province, Indonesia. In the study area, a cavity zone is exposed at the wall of quarry bench and occurs by a solution process. The cavity layer zone is a weak zone which has caused bench failures. The objective of this research is to evaluate the quality of the cavity limestone layer for a safe mine design using Rock Mass Rating (RMR) system. Final result of the research is a rock mass characterization, specifically for the cavity limestone layer. Keywords: Rock mass rating, limestone, cavity layer